Sinergitas Pemerintah Kabupaten Sidoarjo dengan Kodim 0816 Sidoarjo Dalam Upaya Pemulihan Ekonomi di Masa Pandemi Covid-19 - Dewi Kurniasih; Aulia Zharifah (Jurnal Pemerintahan dan Politik Lokal, 2022)
The aims of this study is to analyze the synergy between the Sidoarjo Regency Government and the 0816 Sidoarjo Kodim in an effort to recover the economy during the Covid-19 pandemic. The research method we use is a qualitative-phenomenological approach. The results of the study, among others, show that the synergy between the Sidoarjo Regency Government and the Military Unit in this case the 0816/Sidoarjo Kodim has been running quite optimally. The available resources are sufficient, apart from that, the partnership relationship is also quite good. The characteristics of partners in the synergy of Government sidoarjo Regency and Kodim 0816/Sidoarjo in an effort to recover the economy during the Covid-19 pandemic in Sidoarjo Regency are quite optimal. The partnership relationship in the Synergy of Government sidoarjo Regency and Kodim 0816/Sidoarjo in Handling Covid-19 in Sidoarjo Regency is quite good. The characteristics of the partnership in the Synergy of of Government sidoarjo Regency and Kodim 0816/Sidoarjo in Handling Covid-19 in Sidoarjo Regency are quite good. It seen from the leadership of the chairsman of the Task Force for the Acceleration of Covid-19 Response that he was able to provide enlightenment regarding activities. Environmental factors in the synergy between of Government Sidoarjo Regency and Kodim 0816/Sidoarjo in Handling Covid-19 in Sidoarjo Regency are quite conducive. However, what is quite influential is the existence of information that is Hoax and disrupts the level of trust in the Sidoarjo Regency government. Therefore, it is necessary to provide continuous education to the community about COVID-19, socialization so that the community participates in economic recovery efforts, implementation Karya Bakti or Food Security activities, as well as empowering MSME actors to rise again.